Desafios para a gestão da saúde do trabalhador: uma revisão integrativa da literatura - Zagato, Alexandre Ricardo (Universidade Federal de São Carlos, 2016)
In the last decades, several initiatives of the Brazilian society have been trying to consolidate advances in the public policies of integral attention in Occupational Health. The programs and actions in the field of Work Management and Health Education converge towards the consolidation of policies for valuing workers in health. In this context, the objective of this paper was to analyze the challenges that are required to achieve a policy aimed at occupational health, from an integrative literature review. The delimitations of the review were published between 2009 and 2019, searched in the Lilacs and Medline databases. The selected articles were analyzed using an analysis form proposed by the authors and specific considerations were analyzed using the Bardin analysis technique. The articles were grouped into six categories, so it can be understood that Occupational Health goes beyond the limits of occupational health, resulting from a set of political, social and economic factors. Then, when workers 'health is addressed in a way that promotes workers' health and reduces risks and health problems, through prevention, financial, structural and governmental incentives, training and updates of health professionals, there will be improvement in all limitations presented.
Challenges for occupational health management: an integrative literature review
Keywords: Saúde do trabalhador; Saúde ocupacional; Doenças ocupacionais; Occupational health; Occupational health; Occupational diseases; CIENCIAS DA SAUDE::SAUDE COLETIVA